BANKING MARKET STRUCTURE AND GROWTH: CASE OF INDONESIA - RATNA DERINA; ANNA SN DASRIL (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The principle objective of this paper is to investigate the empirical relevance of the impact of economic and financial crisis on market structure of banking sector and economic growth. The study shows that the relationship between market structure and economic development changes in the period of before and after the crisis. Before the crisis, the market structure negatively affects the economic growth. After the crisis market structure of the banking industry promotes the growth in the economy. We also find that credit channeled by banks to domestic manufacturing industry is not adequate enough to support the economic growth to the level prior the crisis.